The Key to Study Success: Self-Regulation and Academic Adjustment at Satya Wacana Christian University - Tasiabe, Hilman Richard; Rahayu, Maria Nugraheni Mardi (Psikoborneo: Jurnal Ilmiah Psikologi, 2024)
Early adulthood is a transition period from adolescence to adulthood. This adult period starts from the age of 18 – 25 years at which time you have entered the world of college as a student. The main task of being a student is to learn with all the obstacles one faces actively and critically. Changes in the learning environment at school with lectures result in many things that students have to adjust to, such as learning styles, friendships and social situations, as well as dealing with lecturers. This research uses quantitative correlational methods. A total of 77 students from the class of 2022 at Satya Wacana Christian University were involved in this research. The results showed that academic adjustment had a significant positive relationship with self-regulation (r=0.527, sig.=0.000). Thus, it can be concluded that the results of this research show that there is a significant relationship between self-regulation and academic adjustment of students class of 2022 at Satya Wacana University. This means that the higher the self-regulation, the higher the academic adjustment of the class of 2022 students at Satya Wacana University, and vice versa. The implications of this research are that universities and faculties can develop programs that can improve self-regulation in new students so that their academic adjustment will be better.Masa dewasa awal merupakan masa peralihan dari masa remaja menuju masa dewasa. Masa dewasa ini dimulai dari usia 18 – 25 tahun yang mana usia ini sudah memasuki dunia perkuliahan sebagai mahasiswa. Tugas pokok menjadi seorang mahasiswa adalah belajar dengan segala rintangan yang dihadapinya secara aktif dan kritis. Perubahan lingkungan belajar di sekolah dengan perkuliahan mengakibatkan banyak hal yang harus disesuaikan oleh mahasiswa, seperti gaya belajar, pertemanan dan sosial, serta menghadapi dosen. Penelitian ini menggunakan metode kuantitatif korelasional. Sebanyak 77 mahasiswa angkatan 2022 Universitas Kristen Satya Wacana terlibat dalam penelitian ini. Hasil penelitian menunjukkan bahwa penyesuaian akademik memiliki hubungan positif signifikan dengan regulasi diri (r=0,527, sig.=0.000). Dengan demikian dapat disimpulkan bahwa hasil penelitian ini menunjukkan bahwa terdapat hubungan signifikan antara regulasi diri dan penyesuaian akademik mahasiswa angkatan 2022 Universitas Satya Wacana. Hal ini berarti semakin tinggi regulasi diri, maka semakin tinggi pula penyesuaian akademik mahasiswa angkatan 2022 Universitas Satya Wacana, dan begitu pula sebaliknya. Implikasi dari penelitian ini universitas dan fakultas dapat mengembangkan program yang dapat meningkatkan regulasi diri pada mahasiswa baru sehingga penyesuaian akademik mereka akan semakin baik.